Modelling a strategic use of records as strategic resource in the Malaysian public sector / Mohammad Azhan Abdul Aziz ... [et al.] - Abdul Aziz, Mohammad Azhan; Hussin, Norhayati; Abdul Rahman, Abd Latif; Mohamad Rosman, Mohamad Rahimi; Ab. Ghani, Nor Azlina (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Record surely can be identified in most organizations but the practices of record management may be only some of the organizations are familiar with it. Hence, records ought to be overseen as a vital asset to encourage the daily function and operation of the organization. Record as a strategic resource is defined that records as a medium to improve the effectiveness and efficiency of the organization, it becomes a strategic resource that provides for future use. The study aims at describing how public records are managed and used among officers in departments and ministries of the Malaysian government. The respondents and key informants engaged in this study are Diplomatic Administer Officer (PTD) from different position grades starting from grade M44 to JUSA because they are categorized as top management that acts as administer, policymaker, decision-maker, etc. in the organization. The respondents were randomly selected from twelve ministries and one department of the Malaysian public sector in Putrajaya. Findings show that all hypotheses are accepted. Records users as found to have a significant and positive relationship with strategic use of records. Records value was also found to have a significant and positive relationship with strategic use of records same as the relationship between records user and records value. Moreover, records value is hypothesized as a mediator between records user and strategic use of records also indicate the same result. The results of the study have contributed to the development of research model and theory in using records as a strategic resource especially, in the government sector. Government servants especially PTD officers must use records as one of the strategic resources in carrying out their daily affairs. Systematic record management needs to be further strengthened to ensure that the preserved memory of corporate enemies contributes to the development of a developed and rapid nation.